1997
DOI: 10.1029/96jd02031
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐instrument zenith observations of noctilucent clouds over Greenland on July 30/31, 1995

Abstract: Abstract. Results are presented for zenith observations of a noctilucent cloud (NLC) display over the Sondrestrom atmospheric research facility near Kangerlussuaq, Greenland, on July 30/31, 1995. The observations were made with a Rayleigh lidar, which measured the NLC particle volume backscatter coefficient, and with a UV spectrograph, which measured the intensity and degree of linear polarization of solar light scattered from the NLC. The intensity and polarization measurements were made at solar depression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Experimental evidence that short-period GW activity is inversely proportional to PMC backscattering was provided by Gerrard et al (1998Gerrard et al ( , 2004; see also Thayer et al, 2003) using lidar backscatter measurements at Sö ndrestrom, Greenland. Other observations from Sö ndrestrom have also shown evidence of GWs causing PMC sublimation (Hecht et al, 1997). Thayer et al (2003) reproduced the measured weaker PMC backscatter and thinner clouds using a model that included short-period GWs.…”
Section: Introductionmentioning
confidence: 61%
“…Experimental evidence that short-period GW activity is inversely proportional to PMC backscattering was provided by Gerrard et al (1998Gerrard et al ( , 2004; see also Thayer et al, 2003) using lidar backscatter measurements at Sö ndrestrom, Greenland. Other observations from Sö ndrestrom have also shown evidence of GWs causing PMC sublimation (Hecht et al, 1997). Thayer et al (2003) reproduced the measured weaker PMC backscatter and thinner clouds using a model that included short-period GWs.…”
Section: Introductionmentioning
confidence: 61%
“…It has been suggested that GWs cause PMC brightness to vary through wave-induced undulation of cloud layers and wave-induced convergence and divergence of cloud particle concentration (Jensen and Thomas, 1994), through wave breaking (Fritts et al, 1993), or through wave-induced temperature perturbations in the PMC vicinity (Turco et al, 1982;Jensen and Thomas, 1994;Rapp et al, 2002). Observations from Sondrestrom, Greenland (67.01N, 50.91W) showed evidence of the passage of acoustic GWs in the mesopause region causing PMC sublimation (Hecht et al, 1997). Gerrard et al (1998Gerrard et al ( , 2004a analyzed the Rayleigh lidar data from Sondrestrom and found that the strength of stratospheric GWs (30-45 km) was negatively correlated with the PMC brightness.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, PMC brightness is more suitable for long-term trend monitoring. However, PMC brightness is strongly influenced by tides (von Zahn et al, 1998;Chu et al, 2001bChu et al, , 2003Chu et al, , 2006Fiedler et al, 2005), planetary waves (Merkel et al, 2003), and gravity waves (GWs) (Hecht et al, 1997;Gerrard et al, 1998Gerrard et al, , 2004a. To derive reliable long-term trends and to understand the meaning of these trends, it is important to understand and quantify PMC brightness response to various dynamic factors in addition to the basic water vapor, temperature, and nucleation parameters.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, over shorter time scales (i.e., less than ∼day) these waves are believed to be responsible for the MC's overall "banded" structure and the potential destruction of such clouds (e.g., Fritts et al, 1993;Jensen and Thomas, 1994;Hecht et al, 1997;Rapp et al, 2002). Particularly, it has been shown in microphysical MC models that gravity waves with short periods (less than ∼6 h) and high amplitudes reduce the cloud strength over time scales of several wave periods (e.g., Jensen and Thomas, 1994;Rapp et al, 2002).…”
Section: Introductionmentioning
confidence: 98%